2022
DOI: 10.1186/s12931-022-02265-6
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and risk factors with COVID-19 or influenza in hospitalized asthma patients

Abstract: Background At the time of the SARS-CoV-2 emergence, asthma patients were initially considered vulnerable because respiratory viruses, especially influenza, are associated with asthma exacerbations, increased risk of hospitalization and more severe disease course. We aimed to compare the asthma prevalence in patients hospitalized for COVID-19 or influenza and risk factors associated with poor prognosis with the diseases. Methods This retrospective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…All articles were published from 2020 to 2023, with data on COVID-19 patients from January 2020 onward and data on influenza patients from 2006 onward ( Table 1 ). Most of the data were from retrospective studies, 5,10,1520,2226,2830,3235,3747 2 articles were prospective studies, 31,34 and 3 articles did not specify the type of study. 21,27,36 Four articles specifically studied patients with influenza A, 10,21,31,36 15 articles studied patients with type A/B, 5,15,16,20,2427,30,32,33,37,39,40,47 16 articles did not state the influenza type of patients, 1719,22,23,28,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All articles were published from 2020 to 2023, with data on COVID-19 patients from January 2020 onward and data on influenza patients from 2006 onward ( Table 1 ). Most of the data were from retrospective studies, 5,10,1520,2226,2830,3235,3747 2 articles were prospective studies, 31,34 and 3 articles did not specify the type of study. 21,27,36 Four articles specifically studied patients with influenza A, 10,21,31,36 15 articles studied patients with type A/B, 5,15,16,20,2427,30,32,33,37,39,40,47 16 articles did not state the influenza type of patients, 1719,22,23,28,…”
Section: Resultsmentioning
confidence: 99%
“…Most of the data were from retrospective studies, 5,10,1520,2226,2830,3235,3747 2 articles were prospective studies, 31,34 and 3 articles did not specify the type of study. 21,27,36 Four articles specifically studied patients with influenza A, 10,21,31,36 15 articles studied patients with type A/B, 5,15,16,20,2427,30,32,33,37,39,40,47 16 articles did not state the influenza type of patients, 1719,22,23,28,29,34,35,38,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it has been suggested that biologic therapies for asthma such as omalizumab may be protective against severe COVID-19, 41 previous findings on inhaled corticosteroids and COVID-19 outcomes in asthma patients were inconclusive. [42][43][44] According to the Global Initiative for Asthma (GINA), 45 classification of asthma severity will require information of medication uses and lung function test eg forced expiratory volume (FEV 1 ) measurements, which were unavailable for this study. Nevertheless, inconsistent results have been reported on the association between severe/uncontrolled asthma and severe COVID-19 in adults.…”
Section: Discussionmentioning
confidence: 99%